PERKAWINAN ANAK DI KABUPATEN MAGELANG: Faktor Pendorong, Dampak terhadap Kehidupan Perempuan, dan Tinjauan Maqāṣid al-Syarī‘ah - Evi Hikmah Nurchayati; Diah Arifika; Milna Wafirah (Wahana Islamika Jurnal Studi Keislaman, 2022)
Child marriage remains a social problem with multidimensional impacts, particularly on women. This study aims to analyze the factors driving child marriage, its impact on women's education, health, psychology, and social relations, and examine it from the perspective of maqāṣid al-syarī‘ah. The study used a qualitative approach with empirical juridical in Magelang Regency. Data were obtained through in-depth interviews, questionnaires, observations, and documentation of 28 women who married under the age of 19 and their 28 parents. The results show that family economic factors, parental pressure, socio-cultural norms, and premarital pregnancy are the main drivers of child marriage. The resulting impacts include the interruption of formal education, economic dependence, vulnerability to violence, and health and psychological problems. From the perspective of maqāṣid al-syarī‘ah, the practice of child marriage contradicts the principle of protecting life, mind, offspring, and human dignity. This study emphasizes the importance of a comprehensive approach based on law, social, and religion in efforts to prevent child marriage.